Investigating 18F-FDG PET/CT Parameters as Prognostic Markers for Differentiated Thyroid Cancer: A Systematic Review - Wang, Hongxi; Dai, Hongyuan; Li, Qianrui; Shen, Guohua; Shi, Lei; Tian, Rong (Frontiers in Oncology, 2021)
Aims To determine whether18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) parameters might be prognostic markers for patients with differentiated thyroid carcinoma (DTC). Methods We searched for eligible articles in PubMed, EMBASE (Ovid), Cochrane Library, and ClinicalTrials.gov from inception to February 2021. We included studies addressing the association between 18F-FDG PET/CT parameters and clinical outcomes among patients with DTC. Quality assessment was performed using the Quality in Prognosis Studies (QUIPS) tool. Results A total of 25 studies including 2954 patients (1994 females, 67.5%) were included; 2416 patients (81.8%) had papillary thyroid carcinoma (PTC), and the mean or median follow-up time ranged from 19.1 months to 17.1 years. Thirteen (52.0%) studies were assessed as ‘unclear’ for the domain of study participation. The most common timing of PET/CT scans was after thyroidectomy (in 20 of 25 studies, 80%), especially in patients with an elevated thyroglobulin (Tg) and a negative radioiodine whole body scan (WBS). The most common PET parameter was FDG uptake. Twelve of 17 (70.6%), and 12 of 12 (100%) studies showed an association between PET/CT parameters and disease progression and survival in patients with DTC, respectively. Conclusion 18F-FDG PET/CT parameters alone or combined with other variables can serve as prognostic markers to identify DTC patients with poor outcomes, especially in the setting of an elevated Tg and a negative WBS. Future research is needed to confirm these findings and to examine the prognostic value of PET/CT parameters for DTC patients, considering the heterogeneity in PET/CT parameters, unclear information of patients, and PET/CT-adapted treatment modification.